Interview met E. Mandel over congres KPSU (Gorbatsjov), uitgezonden op 11 en 12 juli 1990 bij Veronique Nieuws - Mandel, Ernest.
Interview met E. Mandel over congres KPSU (Gorbatsjov), uitgezonden op 11 en 12 juli 1990 bij Veronique Nieuws.